Beneficial Effects of Gracillin From Rhizoma Paridis Against Gastric Carcinoma via the Potential TIPE2-Mediated Induction of Endogenous Apoptosis and Inhibition of Migration in BGC823 Cells - Liu, Wenming; Wang, Yanting; Chen, Junjie; Lin, Zhenhe; Lin, Mengjie; Lin, Xiantong; Fan, Yanyun (Frontiers in Pharmacology, 2021)
Tumor necrosis factor-α inducible protein-8 (TIPE2), initially recognized as a negative immune regulator, exerts an important role in suppressing the progression of numerous cancers. In our previous investigation, we found that TIPE2 expression displayed a decrease or absence in gastric tumor tissue, and the overexpression of TIPE2 suppressed the growth of gastric cancer tumors and cells, demonstrating that TIPE2 could be a potential medicinal target for gastric cancer treatment. However, it’s seldomly reported that several medicinal agents or candidates targeted TIPE2 for treating diseases, including gastric cancer. To identify the candidate targeting TIPE2 to fight against gastric cancer, several extractions from traditional natural medicinal plants with anti-tumor functions were employed to screen the active compounds according to bioassay-guided isolation. Interestingly, gracillin, a component from the ethyl acetate extraction of Rhizoma Paridis, was identified to induce the expression of TIPE2 and inhibit the cell proliferation in gastric cancer BGC-823 cells. Furthermore, the underlying mechanisms that restrain gastric cancer were evaluated by clone formation, EdU staining, flow cytometry, and other assays. Meanwhile, the role of TIPE2 in the anti-tumor effect of gracillin was elucidated via the use of siTIPE2 RNA. It was determined that gracillin could fight against gastric cancer cells by inhibiting the cell proliferation participated by the PI3K/AKT pathway and cell cycle arrest, suppressing the EMT pathway-regulating cell migration, and inducing bcl2-associated mitochondrial apoptosis. Additionally, TIPE2 maybe contribute to the benefits of gracillin. These results of the present study are an important step toward the medicinal development of gracillin, and are also of use in understanding the effect of TIPE2 as a potential tumor target.